The significance of Ethel Browne's research on Hydra for the organizer concept - Holstein, Thomas W. (Cells & development, 2024)
This article focuses on the roots of the organizer concept, which was developed by Hans Spemann during his studies of early embryonic development in amphibians. The fundamental properties of this axis-inducing signaling center have been elucidated through pioneering molecular research by Eddy De Robertis' laboratory and other researchers. Evolutionary comparisons have disclosed the presence of this signaling center, involving the interaction of Wnt and TGF-beta signaling pathways, existed not only in vertebrates but also in basal Metazoa such as Cnidaria. - Notably, even prior to the groundbreaking experiments conducted by Hilde Mangold and Hans Spemann, Ethel Browne conducted similar transplantation experiments on Hydra polyps. They were performed under the guidance of Thomas H Morgan and in the laboratory of Edmund B Wilson. Howard Lenhoff was the first to draw connections between Ethel Browne's transplantation experiments and those of Spemann and Mangold, igniting a vivid debate on the precedence of the organizer concept and its recognition in Nobel Prize considerations. This review critically compares the experiments conducted by Spemann and Mangold with those preceding their seminal work, concluding that the organizer concept clearly builds upon earlier research aimed at understanding developmental gradients, such as in the simple model Hydra. However, these approaches were not pursued further by Morgan, who shifted his focus towards unraveling the genetic control of development in flies, an approach that ultimately revealed the molecular identity of the Spemann organizer in vertebrates.
Online verfügbar: 27 Februar 2024, Artikelversion: 12 August 2024
Gesehen am 27.02.2025